The Role of AI-Powered Assessment Tools in Improving Educational Feedback in Nigeria - Attah Emmanuel Ojoma (International Journal of Education Sciences, 2026)
Educational systems in Nigeria face a persistent challenge in delivering high-quality, timely, and personalized feedback, due primarily to large class sizes, heavy teacher workloads, and reliance on traditional assessment methods. This study investigates the potential of integrating Artificial Intelligence (AI)-powered assessment tools to overcome these systemic barriers and improve the quality of educational feedback within the Nigerian secondary school context. Employing a quantitative cross-sectional survey design, data was collected from teachers and students across three geopolitical zones. Statistical analyses, including regression modeling, were used to test the influence of AI tools on feedback quality and student outcomes. The findings strongly indicate that AI-driven automated grading significantly enhances the timeliness of feedback, allowing students to correct misconceptions while the learning experience is still fresh. Moreover, the use of AI diagnostic reports was found to be highly effective in increasing feedback specificity and personalization. Crucially, the study confirms that teacher training and digital literacy play a vital moderating role, significantly amplifying the positive effect of AI tools on student engagement and performance. The results affirm AI’s transformative potential for secondary education in Nigeria, underscoring the need for policy that prioritizes teacher capacity building alongside technological adoption to ensure equitable and effective implementation.
Keywords: Artificial Intelligence (AI); Nigeria; assessment tools; educational feedback; teacher training